Deficiency Causing Mutations and Common Polymorphisms in the Factor XIII-A Gene - Muszbek, L. (Thrombosis and Haemostasis, 2000)
Blood coagulation factor XIII (FXIII), for its unique features, used to be considered a stepchild among clotting factors. In contrast to other proenzyme clotting factors, it is the precursor of a transglutaminase and not of a proteolytic enzyme. By cross-linking peptide-bound glutamine and lysine side chains transglutaminases make, rather than break, peptide bonds. Activated FXIII (FXIIIa) cross-links fibrin α-chains and γ-chains and covalently attaches α2-plasmin inhibitor to fibrin α-chains to strengthen fibrin mechanically and to protect it from fibrinolysis. In addition to being a clotting factor, FXIII is also an intracellular proenzyme present in platelets and monocytes/macrophages. The plasma factor is of heterotetrameric structure consisting of two potentially active A (FXIII-A) and two inhibitory/protective B (FXIII-B) subunits (A2B2), while its cellular counterpart is a dimer of FXIII-A. Plasma FXIII is activated by the concerted action of thrombin and Ca2+. Thrombin cleaves FXIII-A at Arg37-Gly38, then in the presence of Ca2+ FXIII-B dissociates and FXIII-A assumes an active configuration (reviewed in ref. 1).